2018
DOI: 10.1111/pbi.12929
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting genomic hotspots underlying seed protein, oil, and sucrose content in an interspecific mapping population of soybean using high‐density linkage mapping

Abstract: SummaryThe cultivated [Glycine max (L) Merr.] and wild [Glycine soja Siebold & Zucc.] soybean species comprise wide variation in seed composition traits. Compared to wild soybean, cultivated soybean contains low protein, high oil, and high sucrose. In this study, an interspecific population was derived from a cross between G. max (Williams 82) and G. soja (PI 483460B). This recombinant inbred line (RIL) population of 188 lines was sequenced at 0.3× depth. Based on 91 342 single nucleotide polymorphisms (SNPs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
80
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 103 publications
(90 citation statements)
references
References 83 publications
5
80
0
Order By: Relevance
“…35-35.95 Mb on Chr. Twenty for seed oil content [14,[21][22][23][24][25] and the QTL region of 44.58-48.58 Mb on Chr. Fourteen for seed linolenic acid [11,13,24,26].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…35-35.95 Mb on Chr. Twenty for seed oil content [14,[21][22][23][24][25] and the QTL region of 44.58-48.58 Mb on Chr. Fourteen for seed linolenic acid [11,13,24,26].…”
Section: Introductionmentioning
confidence: 99%
“…With the completion of the genome sequencing of soybean cv. Williams 82 [29] and the rapid development of next-generation sequencing (NGS) technology, singlenucleotide polymorphism (SNP) markers have been used to construct high-density linkage maps to identify QTL intervals [25,30]. Based on a high-density genetic map consisting of 2062 SNP markers, Cao et al (2017) identified one QTL, qOil-5, for seed oil, which was mapped to Chr.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations